Moocs Readiness Among Faculty Members In A Higher Education Institution In Oman - Marhoon Al-Mamari, Hilal Salim (2023)
Many higher education institutions worldwide have used massive open online courses (MOOCs). However, are faculty members in higher education institutions ready to adopt MOOCs for teaching and learning, and what factors influence their readiness to adopt MOOCs? This study attempts to identify factors that affect MOOC adoption among faculty members in Omani higher education institution by focusing on internal factors, external factors, and the moderating effect of gender. The internal factors are personal drivers such as attitude towards MOOCs, self-efficacy and belief towards goal, pedagogy defined as experience with online teaching and learning, and technical factors described as technology competencies and access to tools. Likewise, external factors are defined by subjective norms referring to peer and colleague support, followed by university factors focusing on administrative support and ICT infrastructure. A quantitative correlational method using a survey questionnaire was employed to collect the data among 348 faculty members at Sultan Qaboos University (SQU) and analyzed using partial least squares structural equation modelling (PLS-SEM). Findings showed that the factors influencing MOOCs readiness (MR) are attitude towards MOOCs, self-efficacy, and administrative support. However, belief towards goal and experience with online teaching and learning negatively affects MOOC readiness. Furthermore, internal factors were found to be a better predictor of MOOCs readiness as the model predicted 55.6% of MR where factors such as access to tools, information and communication (ICT) infrastructure and peer and colleagues support were found not to influence their readiness.